1998
DOI: 10.1016/s0014-5793(98)00161-6
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidative damage to cardiac mitochondria: cytochrome oxidase and cardiolipin alterations

Abstract: Rat heart mitochondrial membranes exposed to the free radicals generating system tert-butylhydroperoxide/Cu 2+ undergo lipid peroxidation as evidenced by the accumulation of thyobarbituric acid reactive substances. Mitochondrial lipid peroxidation resulted in a marked loss of both cytochrome c oxidase activity and cardiolipin content. The alterations in the properties of cytochrome c oxidase were confined to a decrease in the maximal activity (V m x ) with no change in the affinity (K m ) with respect to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
73
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 22 publications
3
73
0
1
Order By: Relevance
“…First, the previously reported lesions in Complex III are only present in the IFM [11,[27][28][29]. Because Complex III is one of the primary sites for electron leakage, its decline would likely result in heightened production of reactive oxygen species [11].…”
Section: Discussionmentioning
confidence: 97%
“…First, the previously reported lesions in Complex III are only present in the IFM [11,[27][28][29]. Because Complex III is one of the primary sites for electron leakage, its decline would likely result in heightened production of reactive oxygen species [11].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, cardiac CL deficiencies have been reported in several cardiac pathologies associated with mitochondrial respiratory dysfunction and have been linked specifically to decreased COx activity in hypothyroidism (55), aging (22), and free radical stress (56). Interestingly, Yamaoka-Koseki, Urade, and Kito (52) found that delipidated bovine COx activity was stimulated only by reconstitution with L 4 CL-enriched CL fractions, and not L 4 CL-deficient fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Containing cardiolipin, a phospholipid essential for function [107], the decrease in activity of COX associated with I/R may be in response to hydrolysis [108] or lipid peroxidation of cardiolipin [109,110]. Specific to the subsarcolemmal mitochondria [111], the modification status of cardiolipin could be identified readily using numerous proteomic techniques, with high emphasis on mass spectrometric-based characterization.…”
Section: Changes In Mitochondrial Function and Protein Abundancementioning
confidence: 99%